PENDIDIKAN KESEHATAN NUTRISI IBU HAMIL DENGAN INOVASI PENGOLAHAN KROYAM (KROKET, KENTANG, AYAM, WORTEL, BAYAM,). - Sri Untari; Rizki Sahara; Nurya Kumalasari; Nur Fatimah; Nurul kodiyah; Dhiyan Nany Wigati; Meity Mulya Susanti; Riska Indriyati (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2025)
Background: Nutrition is the intake of nutrients from food and drinks that support health and cell development. For pregnant women, proper nutrition is crucial for both maternal health and fetal growth. However, their knowledge about pregnancy nutrition needs improvement. This community service activity aims to increase pregnant women's awareness of proper nutrition and introduce nutritious local foods like Kroyam (croquettes made from potato, chicken, carrot, and spinach) and orange juice. Methods : included health counseling on nutrition for pregnant women, accompanied by demonstrations on healthy food preparation. Evaluation was conducted through pre-tests before counseling and post-tests after counseling. This activity was carried out at the Pilang Payung Village Hall, Toroh District, Grobogan Regency, with 18 pregnant women participating. Results: From the counseling session, it was found that 18 pregnant women experienced an increase in the knowledge category, namely 18 respondents (100%). Conclusion: Through the implementation of the "Nutrition Health Education for Pregnant Women and Processing of Kroyam (Croquettes, potatoes, chicken, carrots, spinach) can be concluded that the community's understanding of nutrition is still uneven, so that service activities such as this still need to be carried out continuously to ensure the correctness and accuracy of information regarding efforts to improve nutrition in pregnant women with innovations in processing chicken croquettes and orange juice to reduce KEK